「反思性對話」運用於在職教保服務人員專業成長之探究 Inquiry of Reflective Conversations Applied to In-service Preschool Teachers' Professional Development - 張素貞 Su-Chen Chang (National Changhua University of Education, 2020)
本研究旨在探究「反思性對話」運作的歷程與促進教保服務人員專業的開展。關於反思性對話運作的概念，理念層面主要以文獻探討作為立論的根基，並輔以在現場實務層面的運作歷程，研究者透過現場觀察、深度訪談、研究者和參與者的反思札記以及教保服務人員的教學相關對話與文件，歷時一年進行資料的蒐集，並以主題分析法進行分析，以獲得反思性對話運作策略與促進教保服務人員專業發展的情形。本研究發現反思性對 話的方法與策略為：反思性對話的進行需建立在信任的關係基礎，內容從參與者的經驗開始切入，讓教保服務人員對反思性對話意涵與運作有所知覺，強調教保服務人員與專業文本進行反思與對話的歷程，鼓勵教保服務人員對其「意識流」有所覺察、強調「教學中」與「教學中反思之交互作用的再思」之對話運作，透過由口說、書寫、自我、社群、專業（理論）文本與交相運作後的反思與對話；而個案教保服務人員專業開展的情形為：從無意識耗時耗力的反思，逐漸到具覺察性的習慣性反思、教師課程意識的提升與反思性教學實務，激發出教師的教學熱情。 The aims of this study were to explore the mechanics of reflective conversations and promote the practice of reflective teaching among pre-school teachers. To examine the concept of reflective conversations, we conducted a literature review to develop the theoretical framework and observed reflective conversation practices on-site to obtain practical insights. Over a period of one year, we collected data from on-site observations, in-depth interviews, reflective journals kept by the researchers and participants, teaching-related conversations, and documents of preschool teachers. The collected data subsequently underwent thematic analysis to determine strategies of reflective conversation practices and to provide suggestions for promoting preschool teachers' professional development. The methods of reflective conversations determined in this study are outlined as follows： developing reflective conversations through a trust-based relationship；initiating conversations with topics that a participant is familiar with；encouraging pre-school teachers to understand the meaning and mechanics of reflective conversations, to use professional texts for the reflection and conversation processes, and to pay attention to their streams of consciousness；emphasizing the mechanics of conversations developed between the teaching process and the reinterpretation of the reflections on their teaching；and developing reflections and conversations through the interaction between speaking, writing, self, communities, and professional（theoretical）texts. By observing the reflective teaching practices of the teacher participants, we obtained the following findings： initially, the teachers found reflections to be a time-consuming and demanding process and did not develop an awareness of their reflections；however, the teachers developed an awareness of and became accustomed to their reflections gradually. Moreover, increasing teacher awareness of courses and their reflective teaching practices might stimulate their enthusiasm toward teaching.